Penerapan dan Solusi Menghadapi Tantangan Kurikulum Integritas dalam Pembelajaran Pendidikan Agama Islam di MTS Pesantren Asasul Huda - Aas Siti Aisyah; Zakariyah Zakariyah; Ashari Ashari (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
This study aims to analyze the implementation of the integrity curriculum in Islamic Religious Education (PAI), identify the challenges encountered, and formulate solutions to enhance its effectiveness at MTs Pesantren Asasul Huda. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews with the principal, vice principal for curriculum affairs, Islamic Religious Education teachers, and pesantren administrators, as well as relevant documentation. Data analysis was conducted through data condensation, data display, and conclusion drawing, while data validity was ensured through source and time triangulation. The findings reveal that the integrity curriculum is implemented by integrating the values of honesty, responsibility, discipline, trustworthiness, and social awareness into the planning, implementation, and evaluation of Islamic Religious Education learning. The implementation is further strengthened through religious habituation activities, teacher role modeling, pesantren programs, and a school culture oriented toward character development. The main challenges include limited teacher competence in holistically integrating integrity values, insufficient instructional materials, limited supporting facilities, and diverse socio-cultural backgrounds of students. To address these challenges, the madrasah has implemented teacher training programs, developed local curriculum guidelines, strengthened collaboration with parents, and conducted continuous evaluations of students’ character development. This study concludes that the successful implementation of an integrity curriculum requires synergy among teachers, schools, pesantren, families, and the broader social environment to foster students who possess strong character, noble morality, and integrity.